Learning and forgetting processes in Parkinson's disease:: A model-based approach to disentangling storage, retention and retrieval contributions - Faglioni, P; Botti, C; Scarpa, M; Ferrari, V; Saetti, M.C (Neuropsychologia, 1997)
Learning and forgetting a prose passage was studied in 20 patients with Parkinson's disease and in 20 normal control subjects by means of stochastic models, with the aim of identifying the learning and retaining abilities that are affected by Parkinson's disease. Results suggested that Parkinson's disease patients are impaired in developing automatic processing both during learning and retaining, while functions that require active attention are spared. The automatic/intentional dissociation, which is the hallmark of the motor disturbance in Parkinson's disease, extends to memory abilities, and, on the grounds of neuroanatomical, neurochemical and neurophysiological correlates, suggests that the memory deficit in Parkinson's disease may be contingent on a dysfunction of the medial prefrontal–cingulate cortex. © 1997 Elsevier Science Ltd. All rights reserved.